A RETROSPECTIVE STUDY OF FINDINGS AND CHALLENGES IN CONDUCTION OF COVID-19-POSITIVE AUTOPSIES - KAUL, MANPREET; SINGH, JASPINDER PRATAP; KUMAR, KULDIP; BASRA, SUNNY (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: In this article, we report our observations as well as the innovations which were adapted in the resource-limited settings which are present in most parts of the country. The standard protocols were adopted for complete COVID-19 autopsies that were conducted. Methods: The present retrospective study was conducted in the Department of Forensic Medicine and Toxicology, Government Medical College, Amritsar. The medicolegal autopsies were conducted completely in confirmed positive COVID-19 cases. In the medicolegal cases, complete autopsies were conducted, where the investigating officers did not forgo the autopsy. A total of ten COVID-positive autopsies were conducted from July 2020 to August 2021. Results: Gross findings of various organs during autopsy include that of lungs showing relatively unremarkable lungs with mild edema and consolidation, brain showing edema, and subarachnoid hemorrhage, pancreas showing necrotic and hemorrhagic changes, and kidneys flea-bitten and were contracted. Conclusion: Although a complete autopsy is desired to provide the best possible understanding of the disease process, its variants, such as core biopsies and echopsies, can be taken up as safer alternatives, especially in resource-limited centres. Experience, preparation, and experience are the significant vital aspects which help in managing the COVID-19-positive autopsy. The institution needs to develop guidelines as well as standard operating procedures for the smooth and safe conduct of autopsies in COVID-19 dead bodies.